Comparison between 75-g and 100-g oral glucose tolerance tests using international association of diabetes and pregnancy study group one-step diagnostic threshold to detect gestational diabetes mellitus - Zhou, Li-Li; Liu, Dong; Song, Hong-Qing; Wu, Yuan-Bo; Hu, Wei-Bing; Wang, Jian-Feng; Wang, Jin-Sheng; Qi, Chun-Yan; Liu, Sa-Sa (Frontiers in Endocrinology, 2025)
BackgroundThe oral glucose tolerance test (OGTT) is the primary screening method for gestational diabetes mellitus (GDM), but global implementation criteria remain inconsistent.MethodsThis retrospective study analyzed data from 3,907 pregnant women at Tongchuan People’s Hospital, including 1,925 in the 75g OGTT group (430 with GDM) and 1,982 in the 100g OGTT group (460 with GDM). A systematic comparison was conducted between the two groups regarding: blood glucose levels at each time point (0h, 1h, 2h);diagnostic rates, positive composition ratios of gestational diabetes mellitus, and risks of adverse maternal and neonatal outcomes based on the International Association of Diabetes and Pregnancy Study Groups (IADPSG) diagnostic criteria; Correlation analysis of blood glucose levels across time points; A glucose-level-adjusted continuous analysis to evaluate the dose-response relationship between dynamic glucose changes and adverse maternal and neonatal outcomes in the overall population.ResultsThe 100g group had significantly higher 1h and 2h blood glucose levels than the 75g group (p < 0.01);Under the IADPSG criteria, there were no significant differences in GDM detection rates, positive case characteristics, or maternal-neonatal outcomes between the two groups (p > 0.05);Blood glucose levels at different time points were correlated within each group, no glucose rise difference occurred between groups at 0-1h [Difference in slope (95% CI): 0.127 (-0.092 to 0.346), p>0.05]. However, from fasting to 2h, the 100g group showed a steeper rise than the 75g group [Difference in slope (95% CI):0.412 (0.244 to 0.580), p<0.05], and a slower decline between 1-2h [Difference in slope (95% CI):0.047 (0.010 to 0.084), p<0.05].Glucose-adjusted continuous analysis showed that blood glucose levels were mostly associated with adverse outcomes, with the strength of association gradually decreasing from fasting to 1h and 2h. Both groups exhibited similar trends, no significant differences in the risks of adverse outcomes (expressed as ORs) were observed between the 75g and 100g OGTT groups (all p > 0.05).ConclusionUnder the IADPSG criteria, no significant differences in diagnostic efficacy were observed between the 75g and 100g OGTT glucose loads for GDM. Standardizing screening strategies to improve clinical consistency is warranted.